Intellectual capital and performance: testing interaction effects - Kamukama, Nixon; Ahiauzu, Augustine; Ntayi, Joseph M. (Journal of intellectual capital, 2010)
The purpose of this paper is to examine the interaction effect of intellectual capital elements and how they fuse to affect financial performance in microfinance institutions. The major purpose is to explore the appropriate blend or mix of intellectual capital elements that explains the source of value creation – hence performance – in microfinance institutions. Design/methodology/approach – The paper adopts the ModGraph program (Excel version) along with the Kenny and Boran approach to test conditional hypotheses. Findings – The magnitude effect of human capital on performance depends on any of structural or relational capital; hence the assumption of nonadditivity is met. However, no significant interaction effects were established between relational and structural capital. Research limitations/implications – Only a single research methodological approach was employed and future research through interviews could be undertaken to triangulate. Furthermore, the findings from the present study are cross-sectional – future research should be undertaken to examine the multiplicative effects studied in this paper across time Practical implications – In order to boost the wealth of microfinance institutions in Uganda, managers should always endeavor to find a viable intellectual capital mix or blend that can add value to the firm. Originality/value – This is the first study that focuses on testing the interactive effects of intellectual capital elements on financial performance in Ugandan microfinance institutions.
Keywords: Intellectual capital; Financial institutions; Social interaction; Financial performance; Uganda